2018
DOI: 10.3390/molecules23061490
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Analysis of Biochemical Changes in the Serum and Urine of Freund’s Adjuvant-Induced Arthritis in Rats after Treatment with Silkworm Excrement

Abstract: Silkworm excrement (SE), is used as a traditional antirheumatic medicine in China. The present study was designed to investigate the therapeutic efficacy of water fraction of SE (ST) and ethanol fraction of SE (CT) at two different doses on adjuvant induced arthritis (AA) rats. Arthritis severity was evaluated by body weight, paw thickness, histological changes and index of paws oedema and spleen. Serum samples were collected for estimation of biochemical indicators and cytokines. In addition, a metabonomic me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Induction of arthritis was made using the most common method used to evaluate the effects of different types of treatment protocols on inflammatory arthritis which is induction of arthritis using carrageenan solution injected directly into TMJ, carrageenan is polysaccharide obtained from sea weed, it have potent pro-inflammatory effect in animal joint when injected into the joint space 11 , previous studies had proof the carrageenan effectiveness in arthritis induction in TMJ of rats 19,20,24,25 . Pilot study revealed massive edema into TMJ area and decrease amount of food intake by rats suffering from arthritis comparing to normal rats and apparently that decrease in food consumption caused these rats look thinner, thus we made an attempt to evaluate these clinical findings caused by inducted TMJ arthritis and the effect of treatment protocol on head circumference changes caused by edema and weight changes caused by decrease food consumption due to loss proper function of inflamed TMJ.According to our knowledge there was no similar articles available that used head circumference and/or weight changes as clinical parameters for evaluating treatment protocol in induced arthritis, although several authors were report relations between similar parameters and pan-arthritis or joint arthritis (other than TMJ) in human studies as well as animal experimental studies including studies on rats, Vierboom et al, reported significant relation between weight changes and several diseases including arthritis in observational study in human 26 , Leech et al, found relation between lower extremities arthritis with weight and growth in human study 27 , Borb‫י‬ly et al, mentioned significant weight loss in mouse after induction of experimental autoimmunity arthritis 28 ,in the same way Hasan et al, reported similar weight loss in induced paw arthritis inSprague-Dawley rats using complete Freund's adjuvant 29 , identical weight loss secondary to induced arthritis were reported by several authors in Westar rats induced arthritis 21,22,30,32 , also there were several articles used body weight as parameter to assess TMJ function as secondary outcome depending on the fact that limited mouth opening would interfere with normal feeding such as the study of Angelo et al, and Richmond who did randomized clinical trial on Black Merino sheep temporomandibular joint andMiyamoto et al, who used body weight of mice as valuable index for evaluation TMJ diseases 33,35 . As mentioned above no specific head circumference measurement as parameter to evaluate TMJ edema was previously reported, but many authors used similar way to assess edema in arthritic joints by measuring diameters or volume changes, it's good to mention some examples of these techniques; Uttra et al, used Vernier caliper to measure paw diameter to evaluate paw induced arthritis in rats 31 , others relied on volume changes in paws to assess i n d u c e d a r t h r i t i s u s i n g d i s p l a c e m e n t plethysmometry 29,36,...…”
Section: Weight Changesmentioning
confidence: 72%
See 1 more Smart Citation
“…Induction of arthritis was made using the most common method used to evaluate the effects of different types of treatment protocols on inflammatory arthritis which is induction of arthritis using carrageenan solution injected directly into TMJ, carrageenan is polysaccharide obtained from sea weed, it have potent pro-inflammatory effect in animal joint when injected into the joint space 11 , previous studies had proof the carrageenan effectiveness in arthritis induction in TMJ of rats 19,20,24,25 . Pilot study revealed massive edema into TMJ area and decrease amount of food intake by rats suffering from arthritis comparing to normal rats and apparently that decrease in food consumption caused these rats look thinner, thus we made an attempt to evaluate these clinical findings caused by inducted TMJ arthritis and the effect of treatment protocol on head circumference changes caused by edema and weight changes caused by decrease food consumption due to loss proper function of inflamed TMJ.According to our knowledge there was no similar articles available that used head circumference and/or weight changes as clinical parameters for evaluating treatment protocol in induced arthritis, although several authors were report relations between similar parameters and pan-arthritis or joint arthritis (other than TMJ) in human studies as well as animal experimental studies including studies on rats, Vierboom et al, reported significant relation between weight changes and several diseases including arthritis in observational study in human 26 , Leech et al, found relation between lower extremities arthritis with weight and growth in human study 27 , Borb‫י‬ly et al, mentioned significant weight loss in mouse after induction of experimental autoimmunity arthritis 28 ,in the same way Hasan et al, reported similar weight loss in induced paw arthritis inSprague-Dawley rats using complete Freund's adjuvant 29 , identical weight loss secondary to induced arthritis were reported by several authors in Westar rats induced arthritis 21,22,30,32 , also there were several articles used body weight as parameter to assess TMJ function as secondary outcome depending on the fact that limited mouth opening would interfere with normal feeding such as the study of Angelo et al, and Richmond who did randomized clinical trial on Black Merino sheep temporomandibular joint andMiyamoto et al, who used body weight of mice as valuable index for evaluation TMJ diseases 33,35 . As mentioned above no specific head circumference measurement as parameter to evaluate TMJ edema was previously reported, but many authors used similar way to assess edema in arthritic joints by measuring diameters or volume changes, it's good to mention some examples of these techniques; Uttra et al, used Vernier caliper to measure paw diameter to evaluate paw induced arthritis in rats 31 , others relied on volume changes in paws to assess i n d u c e d a r t h r i t i s u s i n g d i s p l a c e m e n t plethysmometry 29,36,...…”
Section: Weight Changesmentioning
confidence: 72%
“…Each animal was weighted before the induction of arthritis and every next day till the end of experiment (eight times) to evaluate weight changes 21,22 , and percentage of weight changes were recorded for each animal.Circumferences of animal head were measured using measuring tape in a circle around the head just anteriorly to the ears in line over TMJs in both sides before the induction of arthritis and every next day till the end of experiment (eight times) to evaluate circumferences changes which represent edema in TMJ 23 and percentage of circumferences changes were recorded for each animal.…”
Section: Clinical Assessmentmentioning
confidence: 99%
“…A total of 1200 μL rat serum sample (20 μL of each rat serum sample) were added to 4800 μL of the working IS solution to generate a quality control (QC) sample for validating the reproducibility of the method and UPLC-QTOF-MS/MS stability [35]. Pretreated samples were vortexed for 3 min, placed on the ice for 30 min, and then centrifuged (15,000 r/min, 4 °C) for 10 min [36,37]. The supernatant was transferred into a sample bottle and stored at 4 °C for MS analysis of untargeted metabolomics.…”
Section: Methodsmentioning
confidence: 99%
“…More than one thousand years ago, herbal doctors had achieved inspiring results by treating difficult miscellaneous diseases with medicinal animal feces. These medicinal feces include Jinzhi originated from human feces 19 , Cansha derived from silkworm feces 20 , and Ambergris produced from cetacean feces 21 , which have been summarized and extensively documented in Compendium of Materia Medica . Influenced by food source, digestive system, age, environment, and other factors, gut microbiotas in different organisms are specific about the abundance and structure, resulting in differences in the content and types of metabolites 22 .…”
Section: Introductionmentioning
confidence: 99%